The impact of the route to diagnosis in nephroblastoma - Mergen, Marvin; Welter, Nils; Furtwängler, Rhoikos; Melchior, Patrick; Vokuhl, Christian; Gessler, Manfred; Meier, Clemens-Magnus; Kager, Leo; Schenk, Jens-Peter; Graf, Norbert (Cancer medicine, 2024)
Introduction Wilms tumor (WT) is the most common childhood kidney cancer. It is a rapid growing embryonal tumor in young children and can be diagnosed with and without tumor related symptoms. Methods We retrospectively analyzed the route to diagnosis of WT treated prospectively according to the SIOP 93-01/GPOH and 2001/GPOH in Germany between 1993 and 2022. Four routes were defined: diagnosis due to tumor-related symptoms, incidental diagnosis during another disease, diagnosis by preventive examinations, and diagnosis within a surveillance program. For these groups we compared clinical and tumor characteristics and outcome. Results Of 2549 patients with WT 1822 (71.5%) were diagnosed by tumor-related symptoms, 472 (18.5%) incidentally, 213 (8.4%) by preventive medical examinations, and 42 (1.6%) by surveillance. Age, general health status, tumor volume, and local and overall stage varied significantly between these groups. The youngest patients were those diagnosed by preventive medical examination (mean: 1.70 years). These patients also showed the best general health status. Tumor volume at diagnosis (549 mL) and after preoperative chemotherapy (255 mL) was significantly higher for children with tumor-related symptoms. The highest percentage of local stage I (78.6%) and the lowest percentage of metastatic disease (4.8%) was found in the surveillance group. The outcome of patients was not significantly different, with up to 19.0% relapses in the surveillance group and 3.0% deaths in the group with tumor-related symptoms. Conclusion The route to diagnosis of WT correlates with age, general health status, tumor volume, and stage distribution, but does not impact the outcome of patients. Nonetheless, diagnosis without tumor related symptoms results in lower treatment burden and thus improved quality of life.
Gesehen am 18.11.2024